2014
DOI: 10.7150/ijms.9303
|View full text |Cite
|
Sign up to set email alerts
|

Automated Sleep Apnea Quantification Based on Respiratory Movement

Abstract: Obstructive sleep apnea (OSA) is a prevalent and treatable disorder of neurological and medical importance that is traditionally diagnosed through multi-channel laboratory polysomnography(PSG). However, OSA testing is increasingly performed with portable home devices using limited physiological channels. We tested the hypothesis that single channel respiratory effort alone could support automated quantification of apnea and hypopnea events. We developed a respiratory event detection algorithm applied to thorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Moreover, if the cutoff value was set at 5/h for both REI_eTST and REI_TIB, the specificities and kappa coefficients for predicting AHI ≥ 5 were clearly low with the 2 REIs. These results suggest that screening of AHI ≥ 5 with the SBV may be difficult, a problem that has been noted with wearable PMs (12,27,28). In contrast, when the REI value was set to 17.0 for REI_eTST or 15.9 for REI_TIB, the sensitivities and specificities for AHI ≥ 15 were good.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, if the cutoff value was set at 5/h for both REI_eTST and REI_TIB, the specificities and kappa coefficients for predicting AHI ≥ 5 were clearly low with the 2 REIs. These results suggest that screening of AHI ≥ 5 with the SBV may be difficult, a problem that has been noted with wearable PMs (12,27,28). In contrast, when the REI value was set to 17.0 for REI_eTST or 15.9 for REI_TIB, the sensitivities and specificities for AHI ≥ 15 were good.…”
Section: Discussionmentioning
confidence: 81%
“…A recent study using tracheal sounds to identify apneas reported 92.8% sensitivity and 99.7% specificity [12]. Using only the thoracic respiratory effort, a comparison based on sleep and wake periods between estimated AHI and scored AHI resulted in a correlation coefficient of r 2 = 0.73 for training and r 2 = 0.55 for validation set [13]. A study estimating AHI using only SpO 2 reported a Cohen's kappa of 0.71 and an accuracy of 91% [4].…”
Section: Discussionmentioning
confidence: 99%
“…Because the level-IV system includes single-or dual-bio-sensor recordings, algorithms use either thoracic, abdominal, or both belt signals (RIPsum). For example, one study developed an OSA detection algorithm that adopts an adaptive envelope-tracking function following the amplitude excursion of a thoracic signal [16]. The tracking function is adaptive in that for each breath, a new threshold is defined based on the height of the previous peak.…”
Section: Related Workmentioning
confidence: 99%